2010
DOI: 10.1007/s10535-010-0070-7
|View full text |Cite
|
Sign up to set email alerts
|

Proline accumulation and the expression of Δ<sup>1</sup>-pyrroline-5-carboxylate synthetase in two safflower cultivars

Abstract: Proline (Pro) accumulation under water stress was measured in safflower (Carthamus tinctorius L.) drought tolerant cv. A1 and sensitive cv. Nira. Activities of pyrroline-5-carboxylate reductase (P5C reductase) and pyrroline-5-carboxylate synthetase (P5C synthetase), two enzymes involved in the Pro biosynthetic pathway were also estimated. Water stress resulted in a reduction in the leaf dry mass and chlorophyll content along with a gradual accumulation of Pro. RT-PCR results show higher expression of ∆ 1 -pyrr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 36 publications
1
5
1
Order By: Relevance
“…In plant cell it has been reported that methionine as a fundamental metabolite through its first metabolite S-adenosylmethionine synthetase [39]. In contrast to our results, Thippeswamy et al [20] reported the water stress tolerance mechanism in safflower was controlled by pro which was due to increased activity of P5CS. In safflower, the range of met is 1.4-1.5%, pro 8.5-9.5% and the range of pro is higher than the met.…”
Section: Overall Amino Acid Distribution In All the Ests Librariescontrasting
confidence: 99%
See 1 more Smart Citation
“…In plant cell it has been reported that methionine as a fundamental metabolite through its first metabolite S-adenosylmethionine synthetase [39]. In contrast to our results, Thippeswamy et al [20] reported the water stress tolerance mechanism in safflower was controlled by pro which was due to increased activity of P5CS. In safflower, the range of met is 1.4-1.5%, pro 8.5-9.5% and the range of pro is higher than the met.…”
Section: Overall Amino Acid Distribution In All the Ests Librariescontrasting
confidence: 99%
“…The unigene sets of all the libraries were searched for SSRs using SSRLocator [18][19][20][21] and the abundance of amino acids predicted from the trinucleotide repeats were compared among all the libraries. SSR locator was used to search SSRs (motifs ranging from 1 to 10 nucleotides) in order to evaluate the pattern of EST-SSR distribution among all libraries.…”
Section: Identification and Comparison Of Est-ssr And Amino Acid Distmentioning
confidence: 99%
“…However, the two distinct committed steps are regarded as rate limiting and two enzymes are γ-GK and γ-GPR. These two enzymes are operative in a sequential manner for biosynthesis of proline and have been evident to relate the redox balance under osmotic stress (Thippeswamy et al 2010). Recently, the effects of cadmium and zinc stress on these enzyme activities have been studied and revealed the regulatory property of proline in homeostasis of ions (Wang et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…There are two proline synthetic pathways in higher plants (Charest and Phan 1990). One is the conversion of glutamate via the action of pyrroline-5-carboxylate synthetase (P5CS) (Voetberg and Sharp ⎯⎯⎯⎯ 1991, Turchetto-Zolet et al 2009, Thippeswamy et al 2010, while the other is the conversion of ornithine (Canas et al 2008, Funck et al 2008) via ornithine aminotransferase (OAT). Conversely, proline can be catabolized to glutamate via the action of proline dehydrogenase (PDH; Kiyosue et al 1996, Peng et al 1996, Verbruggen et al 1996.…”
Section: Introductionmentioning
confidence: 99%